2020
DOI: 10.21203/rs.2.20703/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cause and predictors of neonatal mortality among neonates admitted to neonatal intensive care units in public hospitals in eastern Ethiopia: A facility-based prospective follow-up study

Abstract: Background: The first month is the most crucial period for child survival. Neonatal mortality continues to remain high with little improvement over the years in Sub-Saharan Africa, including Ethiopia. This region shows the least progress in reducing neonatal mortality and continues to be a significant public health issue. In this study setting, the causes and predictors of neonatal death in the neonatal intensive care units are not well documented. Hence, this study aimed to determine the causes and predictors… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 19 publications
9
18
0
Order By: Relevance
“…This finding is supported with the studies done in Libya and in Ethipia, Jigjiga-Sheik Hassan Yabare Referral Hospital, Dessie referral hospitals, Eastern part of Ethiopia public hospitals and Black lion hospital. 10,15,20,21 In fact, prematurely delivered baby faced different complications as a result of difficulty in adapting to extra-uterine environment and consequently are at risk of different complications compared to term babies Therefore, they need more special attention to reduce neonatal mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is supported with the studies done in Libya and in Ethipia, Jigjiga-Sheik Hassan Yabare Referral Hospital, Dessie referral hospitals, Eastern part of Ethiopia public hospitals and Black lion hospital. 10,15,20,21 In fact, prematurely delivered baby faced different complications as a result of difficulty in adapting to extra-uterine environment and consequently are at risk of different complications compared to term babies Therefore, they need more special attention to reduce neonatal mortality.…”
Section: Discussionmentioning
confidence: 99%
“…5 As the prevailing evidence on neonatal mortality was very few to initiate structured intervention, implementation of MDG-4 was unfortunately not effective as planned. 9,10 Subsequently, identifying the magnitude and determining the factors associated with neonatal death is an evidence for inventions and a fundamental to tackle the burden of neonatal deaths. 11,12 However, there was a general shortage of studies on neonatal mortality in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…8 From public hospitals in Eastern Ethiopia, around 28.58% of neonatal deaths were due to preterm complications. 9 In Mizan Tepi University Teaching Hospital (MTUTH), from all neonatal deaths (22.8%), more than two-thirds (76%) of deaths were caused by prematurity. 10 The sustainable development goal three emphasizes reducing neonatal deaths with a goal of 12 neonatal deaths per 1000 live births per country by 2030 through different interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The Ethiopian study put the proportion of neonatal deaths in health facilities at 20%. The causes of neonatal mortality included preterm birth 28.58, birth asphyxia 22.45%, neonatal infection 18.36%, meconium aspiration syndrome 9.18%, respiratory distress syndrome 7.14%, congenital malformations 4.08% 7 . Previous studies reported that neonatal mortality in health facilities was 13.3% or about 30 deaths per 1000 live births.…”
Section: Introductionmentioning
confidence: 99%